Nursing students' knowledge about and attitude toward electroconvulsive therapy: A study from a tertiary care hospital in North India - Bilal Ahmad Bhat (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2020)
Background: Today, electroconvulsive therapy (ECT) has evolved into a modern procedure with a benign side effect profile, which is performed under anesthesia and the administration of muscle relaxants, but the negative view of this treatment is held not only by the general lay public but also by the medical professionals including nurses. Aims: Our aim was to assess the knowledge about and attitude toward ECT in nursing students. Materials and Methods: This was a cross-sectional study in which knowledge about ECT and attitude toward this treatment was assessed in nursing students using ECT knowledge and attitude questionnaires. Statistical analysis was carried out using the Statistical Package for the Social Sciences. Results: A total of 54 3rd-year nursing students were included in the study. More than half (59.3%) reported the primary source of information as media. None of our students had full knowledge about ECT, i.e., score of 31. The mean knowledge score was 16.22 ± 3.36, with a range of 10–21. They were more knowledgeable about the consent, side effects, and procedure part of the questionnaire compared to indications and effectiveness parts of it. Negative attitude toward ECT was highly prevalent. The mean score on attitude questionnaire was −7.5 ± 3.61, with a range of 0 to −12. More than three-quarters of our students had negative attitude in 12 out of 16 items. Total score on knowledge questionnaire and total score on attitude questionnaire were correlated positively (rs= 0.442,P < 0.001). Conclusion: There is a deficiency in knowledge and highly prevalent negative attitude toward ECT among nursing students which needs to be rectified so that ECT becomes a more acceptable treatment procedure.